Interactive Gamification Media Promotes English Vocabulary Acquisition For Secondary School Students: Media Gamifikasi Interaktif Mempromosikan Akuisisi Kosakata Bahasa Inggris Untuk Siswa Menengah - Dina Lisdiani; Din wahyudin; Suyato Kusumaryono (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Lexicon comprehension acts as a fundamental component in language instruction, serving as the basis for effective verbal and written communication. Specific Background However, secondary school learners frequently struggle to acquire new words due to monotonous conventional memorization methods that fail to stimulate active participation. Knowledge Gap Although digital game-based environments offer interactive solutions, empirical investigations explicitly evaluating specific real-time virtual platforms for lexicon instruction remain scarce. Aims This quasi-experimental study investigates the application of an interactive digital medium to facilitate word comprehension and retention among adolescents. Results Statistical analysis of 64 participants revealed that the experimental group utilizing the virtual platform achieved a significantly higher post-test mean score of 82.40 compared to the control group's 70.15, alongside a high N-Gain score of 0.72 and a large Cohen’s d effect size of 1.75. Novelty This research uniquely demonstrates that integrating real-time virtual world elements, such as competitive challenges and instant feedback, transforms passive memorization into a highly engaging cognitive and affective experience. Implications Educators should integrate interactive digital platforms into their pedagogical frameworks to stimulate learner motivation and accommodate modern technological learning demands. Highlights Interactive digital platforms significantly elevate secondary learner test scores and active classroom participation. Experimental groups utilizing virtual challenges achieved a substantial 0.72 N-Gain calculation. Integrating competitive elements and immediate feedback successfully transforms monotonous language memorization routines. Keywords ZEP Quiz; Gamification; Vocabulary Mastery; Educational Media; Interactive Learning